2019
DOI: 10.20473/jops.v3i1.16430
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Intensity of Nematode Infection on The Crossbreed Horse in Detasemen Kaveleri Berkuda Parongpong Bandung West Java

Abstract: This survey study was aimed to determine the prevalance of nematodosis and intensity on the Crossbreed Horse in Detasemen Kaveleri Berkuda Parongpong Bandung West Java. The benefits of this research are to contribute giving additional information about Prevalence, Intensity, and Relation among prevalance with age, sex, and stable. Fecal samples were tested by native, sedimentation, and floatation methods. The examination was found some kind of worm eggs, which are: Trychonema sp., Strongylus spp., Dict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Although studies have reported on the prevalence of gastrointestinal and vector-borne parasitic diseases, such as Piroplasmosis and Trypanosomiasis, of equids in many provinces of Indonesia (Febriyanti et al, 2019;Nugraha et al, 2018;Nurcahyo et al, 2019), to our knowledge there have been no reported studies of such in NTB.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although studies have reported on the prevalence of gastrointestinal and vector-borne parasitic diseases, such as Piroplasmosis and Trypanosomiasis, of equids in many provinces of Indonesia (Febriyanti et al, 2019;Nugraha et al, 2018;Nurcahyo et al, 2019), to our knowledge there have been no reported studies of such in NTB.…”
Section: Introductionmentioning
confidence: 93%
“…Reliance on evaporative cooling in horses is vital for exercise-induced heat production, hence high humidity compromises any cooling effects of sweating (McCutcheon & Geor, 2014;McEwan, Jenkinson, Elder & Bovell, 2006). Given the challenges of working in such a tropical climate, parasitic infections that may result in a range of diseases, including anaemia and hypoproteinaemia, will not only limit the working lives of ponies but may indeed be fatal (American Association of Equine Practitioners, 2019; Febriyanti et al, 2019;Nugraha et al, 2018;Nurcahyo, Yowi, Hartati, & Prastowo, 2019).…”
Section: Introductionmentioning
confidence: 99%